Analysis of Clinical Results of Three Different Routes of Percutaneous Endoscopic Transforaminal Lumbar Discectomy for Lumbar Herniated Disk - Farid Yudoyono; Rully Hanafi Dalan (Neurologico Spinale Medico Chirurgico, 2018)
Objective: Percutaneous endoscopic transforaminal lumbar discectomy (PETLD) can be performed by using foraminal, intervertebral, and suprapedicular routes. The aim of this study was to assess clinical results of three different routes of PETLD. Methods: One hundred and eleven patients who underwent PETLD between January 2016 and October 2016 were included in this study. PETLD was performed using the foraminal (group A), intervertebral (group B), and suprapedicular (group C) routes in 32, 46, and 33 patients, respectively. Outcomes were evaluated using the visual analogue scale (VAS), Oswestry Disability Index (ODI), and MacNab criteria. Results: Seventy-one men and 40 were women (mean age 53.33 ± 14.12 years). The mean follow-up period was 6.44 ± 3.26 months. The preoperative VAS score decreased significantly (P < 0.01) in all 3 groups, but the postoperative VAS score was higher for the foraminal route than the intervertebral (P<0.001) and suprapedicular routes (P < 0.001). Excellent outcome grade according to MacNab criteria was less in foraminal route (18.7%) than in intervertebral (52.2%) and suprapedicular (56.7%) routes. ODI improved significantly (P < 0.01) in all 3 groups. Conclusion: All 3 routes of PETLD resulted in good to excellent clinical results. Nevertheless, the postoperative VAS score was higher for the foraminal route than the intervertebral and suprapedicular routes, probably because of the neurologic characteristics of the disk location. The surgeon should consider this problem to alleviate pain postoperatively and to better counsel the patient before surgery.